Short-term effectiveness of high-load compared with low-load strengthening exercise on self-reported function in patients with hypermobile shoulders: a randomised controlled trial. Issue 22 (1st June 2022) - Liaghat, Behnam; Skou, Søren T; Søndergaard, Jens; Boyle, Eleanor; Søgaard, Karen; Juul-Kristensen, Birgit
Abstract : Objectives: To investigate the short-term effectiveness of high-load versus low-load strengthening exercise on self-reported function in patients with hypermobility spectrum disorder (HSD) and shoulder symptoms. Methods: A superiority, parallel-group, randomised trial (balanced block randomisation, electronic concealment) including adult patients (n=100) from primary care with HSD and shoulder pain and/or shoulder instability ≥3 months. Patients received 16 weeks of shoulder exercises (three sessions/week): HEAVY (n=50, full-range, high-load, supervised twice/week) or LIGHT (n=50, neutral/mid-range, low-load, supervised three times). The primary outcome was the 16-week between-group difference in self-reported function measured with the Western Ontario Shoulder Instability Index (WOSI, scale 0–2100, 0=best, minimal important difference 252 points). Secondary outcomes were self-reported measures including quality of life and clinical tests including shoulder muscle strength and range of motion. An intention-to-treat analysis with multiple imputation was conducted by a blinded biostatistician using linear regression. Results: 93 of 100 patients (93%) completed the 16-week evaluation. The mean WOSI score between-group difference significantly favoured HEAVY (−174.5 points, 95% CI −341.4 to −7.7, adjusted for age, sex, baseline score, clustering around clinic). The secondary outcomes were inconclusive, but patients in HEAVY were less likely to have a positive shoulder rotation test >180°, and more likely to rate an important improvement in physical symptoms. There were no serious adverse events, but HEAVY was associated with more transient muscle soreness (56% vs 37%) and headaches (40% vs 20%). Conclusion: High-load shoulder strengthening exercise was statistically superior to low-load strengthening exercise for self-reported function at 16 weeks and may be used in primary care to treat patients with HSD and shoulder pain and/or instability to improve shoulder function in the short term. Further studies are needed to confirm the clinical relevance, and patients should be supported to manage associated minor adverse events. Trial registration number: NCT03869307 .